1979
DOI: 10.1037/h0077569
|View full text |Cite
|
Sign up to set email alerts
|

Social inhibition of sexual maturation in male prairie deer mice.

Abstract: The sexual maturation of male prairie deer mice (Peromyscus maniculatus bairdii) that were reared with other males was inhibited in comparison with that of males reared in isolation. Inhibition occurred in males reared with nine or four males of the same age, as well as in those housed with one adult male. This phenomenon was observed after several periods of grouping, and consequently at several ages ranging from 5 wk to 4 mo. Females did not retard the sexual development of males. These results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
1
19
2
Order By: Relevance
“…Suppression of reproductive parameters, on the other hand, by male-male pairings was evident in the present study but only statistically significant for testosterone concentrations of LD mice. Inhibitory effects of male-male pairings have been previously described in deer mice (2). The present study suggests that reproductive status can only be modified by social environment during the breeding season in P. leucopus.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Suppression of reproductive parameters, on the other hand, by male-male pairings was evident in the present study but only statistically significant for testosterone concentrations of LD mice. Inhibitory effects of male-male pairings have been previously described in deer mice (2). The present study suggests that reproductive status can only be modified by social environment during the breeding season in P. leucopus.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, reproductive development was stimulated in short-day male juvenile deer mice (P. maniculatus) by the presence of an adult female (35). Pairing juvenile male deer mice with a male inhibited reproductive maturation, whereas pairing with a female slightly enhanced reproductive tract mass, even in breeding (long day) conditions (2,35). These studies suggest that social environment modulates the effects of photoperiod on the reproductive system under certain conditions.…”
mentioning
confidence: 85%
“…Simple measurement of weight or volume of the testis should be adequate in studies requiring only a general index of testicular maturation ; whether the additional cost of histo¬ logical analysis is warranted will depend on the goals of the given investigation. Histological analysis of testes also supports the view that puberty in males is best regarded as a continuous process (Miller, Whitsett, Vandenbergh & Colby, 1977;Bediz & Whitsett, 1979 Cornified spines are present on the surface of the penis in many species of rodents (Hooper, 1959). In rats and hamsters, at least, the presence of spines in the adult male depends upon exposure to testicular androgen during neonatal life and again in adulthood (Beach & Levinson, 1950;Whitsett et al, 1980 …”
Section: General Methodsmentioning
confidence: 69%
“…or their odours, may accelerate or delay the sexual development of young (see Vandenbergh, 1980, for review) but the evidence for similar developmental effects of factors such as the size, relatedness and sex-composition of litter-rearing groups, has received rather less attention (Meisel & Ward, 1981;Agren, 1981;Hill, 1974;Namikas & Wehmer, 1978;Hasler & Nalbandov, 1974). Males reared in all-male group~for example, showed suppressed reproductive development in prairie deermice Peromyscus maniculatus (Bediz & Whitsett, 1979) and impaired reproductive behaviour in adulthood in rats (Hard & Larsson, 1968). Sharpe et al (1973) found no difference in the rate at which female rats reared in all-female or mixed-sex groups reached sexual maturity, but when mated those females reared in mixed litters produced larger litters.…”
Section: Discussionmentioning
confidence: 99%